Asymptomatic Infant Rib Fractures Are Primarily Non-abuse-Related and Should Not Be Used to Assess Physical Child Abuse - Martin J. C. van Gemert; Marianne Vlaming; Steven C. Gabaeff; Peter G. J. Nikkels; H. A. Martino Neumann (MDPI AG, 2023)
Finding infant rib fractures was for many years an almost undisputed proof that physical child abuse took place. Yet, these rib fractures are virtually always occult and asymptomatic and are only identified when looked for, usually with X-rays, from physical child abuse accusations related to, e.g., suspicion of the shaken baby syndrome. In a recent systematic literature review (searched in Cochran, Embase, PubMed and Sociological Abstracts), Güvensel questioned the diagnostic accuracy of rib fractures to be caused by abuse, due to lack of sufficient scientific evidence. Further, there is currently a world-wide disagreement between physicians considering themselves child abuse specialized, and physicians that explore non-abuse-related symptoms that may mimic physical abuse, which, it is hoped, will significantly reduce current unjustified child abuse diagnoses. In an attempt to help resolving this disagreement, we hypothesize that the probability of physical child abuse-related infant rib fractures is significantly lower than the probability of all other possible non-abuse-related causes of occult asymptomatic infant rib fractures, e.g., from birth trauma, prematurity, osteogenesis imperfecta, hypermobile Ehlers-Danlos Syndrome, severe chronic placental pathology (e.g., massive perivillous fibrin depositions and severe chronic histiocytic intervillositis), and vitamin-D deficiency. As method, we attempted to assess the incidence of these various causes of infant rib fractures, in the Netherlands and the USA. The results are that the estimated Dutch and USA physical abuse-related infant rib fracture incidences are at least about 250 and 45 times lower than the sum of all the non-abuse-related estimates. Because these latter rib fractures are occult and asymptomatic, it is likely that (many) more could be out there. In conclusion, occult asymptomatic rib fractures develop perinatally, virtually always as birth trauma, in infants with sufficiently weak bones due to vitamin D deficiency, transmitted by their vitamin D deficient pregnant mothers. This group also includes cortical rib cracks due to deformation forces, with an estimated 186/100,000 incidence. And, despite obvious uncertainties in all estimated incidences, we provided strong evidence that our hypothesis has relevance, implying that the abundant occult asymptomatic rib fractures, when found in infants, should not be used to assess potential physical child abuse.